A Comprehensive Tobacco Control Policy Program in a Mining Industry in Indonesia: Did It Work? - Prabandari, Yayi S.; Bintoro, Bagas S.; Purwanta, Purwanta (Frontiers in Public Health, 2022)
Background: Risk factor controls, including smoking cessation and prevention, impact health costs. This study aimed to describe the Kaltim Prima Coal (KPC), one of Indonesia's largest coal mining operations, comprehensive tobacco control policy program in 2015 and its impact on smoking behavior among the employees. Method: A survey among 404 employees was conducted to assess the impact of the smoke-free KPC programs. In addition to the descriptive analysis, logistic regression was used to measure the association of intention to the smoking behavior change and the association between intention and the determinants using the Theory of Planned Behavior in 102 smokers. Results: A series of tobacco control programs: advocacy, health education, brief interventions for smoking cessation, peer counselor training, media campaigns, and policy regulations were implemented. About 95.5% of the respondents attended the KPC Smoke-Free 2015 programs, and 97.8% reported they already knew that KPC is a total smoke-free area. Nearly 50% of the respondents expressed that the staff complied with the rules and no longer smoked in KPC. Majority of smokers (76.6%) reduced their consumption, and 5.6% of them quit smoking. Among smokers, we found that attitude toward smoking cessation, subjective norm, and perceived control for quitting were related to the intention to stop smoking. Conclusions: The KPC smoke-free policy has been comprehensively implemented. Regulations on smoking and tobacco controls should be maintained, and monitoring should be consistently done. Media campaigns on the regulations and the availability of trained peer educators for smoking cessation help need to be applied continuously.